Functional Characteristics of Egg Consumption in Various Types of Markets Spread in North Sinjai District - Muh. Alief Ikhsan; Bahri Syamsuryadi; Mangalisu, Azmi (Litbang PEMAS Universitas Islam Lamongan, 2024)
This study aims to determine the functional characteristics of egg consumption in various types of markets spread across North Sinjai District. The research design used analysis of variance (ANOVA) according to a completely randomized design (CRD) with 3 treatments and 3 replications. P1: Supermarkets, P2: Traditional Markets, P3: Retailers. This research uses purebred chicken eggs which are consumed with a total of 27 eggs. Parameters in this research are foam power, foam power and foam stability. The result of this research is that the type of market has no significant effect on the value of egg foam, egg foam and egg foam stability. The results of this study on foam power are supermarkets 543.81, traditional markets 673.98, and retail sellers 716.86. The bubble power is 205.67 ml for supermarkets, 222.33 ml for traditional markets and 285.67 ml for retail sellers. The foam stability is 95.72 ml for supermarkets, 94.27 ml for traditional markets and 94.28 ml for retail sellers. The conclusion of this study is that based on the results and discussion it can be concluded that the functional characteristics of eggs greatly influence the temperature and age of the eggs, retail sellers have a high foaming power of 716.86 ml and 285.67 ml of foaming power, whereas good foam stability is found in super markets 95.72 ml.